Highly Flexible and High‐Performance Complementary Inverters of Large‐Area Transition Metal Dichalcogenide Monolayers. Issue 21 (23rd March 2016) - Pu, Jiang; Funahashi, Kazuma; Chen, Chang‐Hsiao; Li, Ming‐Yang; Li, Lain‐Jong; Takenobu, Taishi
Abstract : Complementary inverters constructed from large‐area monolayers of WSe2 and MoS2 achieve excellent logic swings and yield an extremely high gain, large total noise margin, low power consumption, and good switching speed. Moreover, the WSe2 complementary‐like inverters built on plastic substrates exhibit high mechanical stability. The results provide a path toward large‐area flexible electronics.